Older adult healthcare utilization patterns and receptiveness towards Healthier SG Initiative - TAN, Micah (Institutional Knowledge at Singapore Management University, 2022)
The Healthier SG (HSG) initiative was launched by Health Minister Ong Ye Kung in March 2022. HSG marks a distinct departure from existing healthcare models as under this new initiative, greater emphasis is placed on preventive healthcare rather than reactive treatments. This shift in approach is envisioned to have a significant influence on the healthcare system in Singapore – for instance, by focusing on “health care” rather than on “sick care” it is hoped by some that this new model will discourage the ‘over-service’ of patients by doctors in Singapore (Lim, 2022). An integral component of the HSG initiative is the move to encourage Singaporeans to register with a primary physician and visit this physician for most of their healthcare needs (Ministry of Health, 2022). This is in contrast with current tendencies for Singaporeans to ‘doctor hop’, or in other words, to visit multiple doctors over time. What is achieved through the sustained and prolonged relationship between an individual and their family physician or healthcare practitioner over time is what researchers refer to as ‘continuity of care’, where patients are cared for by a single or a small number of professionals. Continuity of care has been argued to result in care that is tailored to an individual’s needs, where illnesses are managed ‘in the context of the patient’s life’ (Gulliford et al., 2006). This move to encourage Singaporeans to register with a primary physician is thus a welcome one as it is likely to result in improved health outcomes among the Singapore population. Continuity of care has been shown to be particularly important for older adult populations due to the greater likelihood for older adults to be in poorer health and to suffer from chronic conditions, thus demanding long-term care (Nyweide et al., 2013; Wolinsky et al., 2010). Given this, the current report examines older adult responses to the newly announced HSG initiative to understand their perspectives on the initiative, as well as their willingness to participate in the initiative.